2014
DOI: 10.1007/s12687-014-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Engaging diverse populations about biospecimen donation for cancer research

Abstract: Clinical research increasingly relies upon the availability of appropriate genetic materials; however, the proportion of biospecimens from racial/ethnic minority patients and healthy controls are underrepresented, which preclude equitable research across all patient groups for cancer treatment. National Cancer Institute-funded Community Network Program Centers in California, Florida, and New York collaborated with local community partners to conduct three independent formative research studies with diverse (Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 35 publications
8
116
0
Order By: Relevance
“…Additionally, Dang et al [2] provided a cross-cultural comparison of three distinct community sites across the USA that collaborated with their local communities on the topic of biospecimen donation participation for cancer research. The sites partnered with participants from African American, three Asian American ethnic groups, as well as diverse Hispanics, and Whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Dang et al [2] provided a cross-cultural comparison of three distinct community sites across the USA that collaborated with their local communities on the topic of biospecimen donation participation for cancer research. The sites partnered with participants from African American, three Asian American ethnic groups, as well as diverse Hispanics, and Whites.…”
Section: Discussionmentioning
confidence: 99%
“…These centers in collaboration with their respective communities examined cognitive, communication, and sociocultural factors affecting biospecimen donation participation. Impediments to community participation in biospecimen donation for cancer research varied by the population(s) studied and included factors concerning cultural beliefs regarding blood or tissue to be donated; some community members described the feeling that research uses them as test monkeys; and others expressed a fear of blood and needles as a deterrent for donating [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, findings from a survey of repository facilities, in the Midwest and Northwest USA, indicated that only 1.3 % of collected biospecimens were from Hispanic participants, compared to 89 % of biospecimens from White participants, and that about half of the surveyed facilities had made efforts to collect biospecimens in their communities (Simon et al 2014). There is an expanding body of literature that documents the significant efforts to engage ethnically and racially diverse communities in biospecimen research across the US (Braun et al 2014;Cohn et al 2014;Dang et al 2014;Dash et al 2014;Erwin et al 2013;Lopez et al 2014;Luque et al 2012;Rodriguez et al 2013). To date, only a few studies have explored biobanking awareness, perceptions, beliefs (Hohl et al 2014;Luque et al 2012;Rodriguez et al 2013), willingness to donate biospecimens (Hohl et al 2014;Lopez et al 2014), and attitudes toward biobanking (Hohl et al 2014) among Hispanic populations in the US.…”
Section: Introductionmentioning
confidence: 99%
“…1–6 In light of the emergence of biospecimen science and the value of samples from diverse populations, two CNPCs—the Tampa Bay Community Cancer Network (TBCCN) and Western New York Cancer Coalition (WNYC2)—realized that educational tools could address an information gap for educating “healthy community members” about this topic. Creating greater understandings about biobanking—for example, What is it?…”
mentioning
confidence: 99%
“…1,10 As such, our two CNPCs embarked on separate but unified journeys to improve understandings and cultural and literacy sensitivities about a new developing technology in oncology, namely, biobanking/biospecimen donation and research. Such communication priming tools could help community, academic, and clinical partners to engage their constituents when making a decision if or when approached to participate in biospecimen donation.…”
mentioning
confidence: 99%